Infralimbic YTHDF1 is necessary for the beneficial effects of acute mild exercise on auditory fear extinction retention. (3rd May 2022) - Li, Song-Ji; Zhang, Lin-Xuan; Zou, Guang-Jing; Ma, Min-Hui; Zhou, Shi-Fen; Lu, Xiao-Yu; Li, Fang; Li, Chang-Qi
Abstract: Exposure therapy is the most effective approach of behavioral therapy for anxiety and post-traumatic stress disorder (PTSD). But fear is easy to reappear even after successful extinction. So, identifying novel strategies for augmenting exposure therapy is rather important. It was reported that exercise had beneficial effects on cognitive and memory deficits. However, whether exercise could affect fear memory, especially for fear extinction remained elusive. Here, our results showed that exposure to acute mild exercise 1 or 2 h before extinction training can augment recent fear extinction retention and 2 h for the remote fear extinction retention. These beneficial effects could be attributed to increased YTHDF1 expression in medial prefrontal cortex (mPFC). Furthermore, by using an AAV-shRNA-based approach to silence YTHDF1 expression via stereotactic injection in prelimbic cortex (PL) or infralimbic cortex (IL), respectively, we demonstrated that silence YTHDF1 in IL, but not in PL, blunted augmentation of exposure therapy induced by acute mild exercise and accompanied with decreased NR2B and GluR1 expression. Moreover, YTHDF1 modulated dendritic spines remodeling of pyramidal neuron in IL. Collectively, our findings suggested that acute mild exercise acted as an effective strategy in augmenting exposure therapy with possible implications for understanding new treatment underlying PTSD.